Effect of Salt in Irrigation Water on Some Physical and Chemical Properties of Lettuce Plant and Soil - YAGMUR*, BÜLENT; AYDIN†, SENAY; OKUR, BÜLENT; COSKUN†, AYSEN (Asian Journal of Chemistry, 2009)
Knowledge of salt tolerance in vegetable plants is necessary to increase productivity and profitability of crop irrigated with saline waters. This research was carried out in Celal Bayar University, Alasehir vocational school glasshouse which is in Manisa, Alasehir located in the west part of Agean region. The purpose of the experiment is to determine salinity effects on some chemical and physical properties of lettuce plant and soil and some vegetative growth parameter of plant which is irrigated with water having different concentrations of salt (NaCl). The experiment was established in a randomized block design with four replications. Salinity levels are in five levels as 0-4-8-12-16 dSm-1 EC. Depending on increasing salt concentration in irrigation water, from the soil saturation extract values, especially Na+ from cations and Cl– from anions which are dominant compared to others (K+, Mg2+, SO42-, HCO3–) and also increase of total soluble salt values have caused some negativeness in plant production. Different EC levels in irrigation water showed an important effect on K+ and Na+ content of soil and only Na+ content of plant. Highest values were generally obtained at 4 dSm-1 EC for lettuce plant vegetative growing parameters such as dry and fresh head weight, head length and leaf number per plant. However, the increase in salt content of water (> 4 dSm-1 EC) affected negatively these vegetative growing parameters.